The Effect of Multinationality, Transfer Pricing, and Thin Capitalization on Tax Avoidance Practices - Putri Amelia Sholichah; Umaimah Umaimah (Universitas Sains dan Teknologi Komputer, 2026)
Tax avoidance remains a significant issue in Indonesia as it affects the optimization of state revenue and the sustainability of national development. Manufacturing companies, as one of the largest contributors to tax revenue, have complex operational characteristics, particularly those engaged in cross-border activities, related-party transactions, and relatively high levels of debt-based financing. Such complexity increases information asymmetry and the potential for aggressive tax burden management. This study aims to examine the effect of multinationality, transfer pricing, and thin capitalization on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. A quantitative approach was employed using multiple linear regression analysis, utilizing secondary data derived from annual financial statements selected through purposive sampling. The results indicate that, to some extent, multinationality and transfer pricing do not affect tax avoidance, whereas thin capitalization has a positive and significant effect. Simultaneously, the three variables significantly influence tax avoidance. The results indicate that, to some extent, multinationality and transfer pricing do not affect tax avoidance, whereas thin capitalization has a significant effect, indicating a lower tendency toward tax avoidance. Simultaneously, all variables significantly influence tax avoidance. These findings suggest that capital structure does not always lead to increased tax avoidance and highlight the complexity of factors influencing corporate tax behavior.